Developing an anaerobic digester with external Zeolite filled column for enhancing methane production from swine manure – A feasibility study. Issue 11 (2nd November 2018) - Wijesinghe, D. Thushari N.; Dassanayake, Kithsiri B.; Scales, Peter; Chen, Deli
ABSTRACT: Development of digesters with an external zeolite column facilitates the convenient removal of the zeolite with TAN, without disturbing the continuous anaerobic digestion process. A digester with an inside zeolite bed (In-Zeo) and digester without adding zeolite (No-Zeo) were employed to compare the process performance with digester with external zeolite column (EX-Zeo). The cumulative, CH4 yields were 5% and 15% greater in the EX-Zeo, and the In-Zeo digesters respectively compared to the No-Zeo digesters. Also, the % VS reduction was 49%, 55% and 41%, respectively in the Ex-Zeo, In-Zeo and No-Zeo digesters. The results indicated that treatment with 7% zeolite during anaerobic digestion has the potential to improve biodegradation of swine manure. The addition of zeolite appeared to reduce TAN from the digestate, thereby enhancing the CH4 yield. Zeolite could be used either internally or externally to enhance CH4 production through anaerobic digestion of swine manure.